In vitro rumen biohydrogenation kinetics of mixed linoleic and alfa-linolenic acids - Castillo Vargas, Julián Andrés; Olivera-Ángel, Martha; Ribeiro, Claúdio Vaz Di Mambro; Daza Caicedo, Edgar Eduardo (Revista Colombiana de Ciencias Pecuarias, 2018)
Background: Dietary linoleic (LA) and alpha-linolenic (LN) acids are extensively isomerized and hydrogenated by rumen microbes, and this activity can further contribute to the fatty acid profile of ruminantderived food products. Objective: To evaluate the effects of LA:LN ratio in lipid supplements on the rumen biohydrogenation kinetics of LA and LN, as well as on the trans-vaccenic acid (VA) production, using an in vitro system. Methods: Rumen fluid was collected from a fistulated steer, diluted with incubation buffer, and then incubated with 500 mg of kikuyu grass (Cenchrus clandestinus) supplemented with 16.3 mg of different LA:LN mixtures (100:0, 75:25, 50:50, 25:75 or 0:100). Incubations were performed in triplicate for a period of 0, 2, 4, 6, 8 or 16 hours. Differences between treatments were evaluated in a completely randomized design. Alternatively, computational chemistry was used to determine the changes in the Gibbs free energy (ΔGrxn) at 39 °C for the principal steps of LA and LN ruminal biohydrogenation. Results: Partial replacement of LA by LN decreased the VA concentration and its accumulation rate; it also increased the stearic acid concentration and the rates of transfer from LA to conjugated linoleic acid (CLA), and from CLA to VA. The conversión from CLA to VA (ΔGrxn = -2.65 kJ/mol) was more spontaneous than that from trans-11, cis-15 octadecadienoic acid (TA) to VA (ΔGrxn = -0.29 kJ/mol). Conclusion: The LA:LN ratio in lipids can modulate LA and LN biohydrogenation (BH) kinetics, as well as the VA production in the rumen.